Abnormal cell cycle regulation in primary human uveal melanoma cultures. - Pardo, M; Piñeiro, A; de la Fuente, M; García, A; Prabhakar, S; Zitzmann, N; Dwek, R; Sánchez-Salorio, M; Domínguez, F; Capeans, C (Wiley, 2004)
Uveal malignant melanoma is the most frequent primary intraocular tumor in adult humans. The cellular events leading to neoplasic transformation of normal uveal melanocytes are not well known when compared to other cancers. In this study, we investigated the role of G1 and G1/S regulatory proteins of the cell cycle in human uveal melanoma (UM) primary cell cultures, since these proteins are common targets in tumor development. Further, freshly established and characterized tumor cells are a better model for in vitro studies when compared to cell lines established long ago. Human primary cell cultures from eight different UM were established, as well as one primary culture from rhesus uveal normal melanocytes (UNM). Primary human UM cultures were characterized by a low establishment and growing rate. From four successful cultures, three showed a high expression of cyclin D1, cyclin E, p16NK4A, and p27KIP1 with no variations in cyclin A, cyclin-dependent kinase 2 (CDK2), and CDK4. Interestingly, in one of the cultured tumors, tumor suppressor protein retinoblastoma (Rb) did not bind E2F despite the fact that Rb was found in its hypophosphorylated form. No mutations in either RB1 or the Rb-binding pocket of E2F-1 were detected. Furthermore, we identified seven proteins co-immunoprecipitating with Rb in this tumor, including Lamin A/C and six proteins not previously reported to bind Rb: Hsc70, high mobility group protein 1 (HMG-1), hnRPN, glyceraldehyde 3 phosphate dehydrogenase (G3PDH), EF-1, and EF-2. Our results indicate that the overexpression of cyclins D1/E and CDKIs p16 and p27, together with a deregulation of the Rb/E2F pathway, may be implicated in the development of human UM.